Keys to the Repository - De la Cruz, Melissa, 1971-; Johnston, Michael (Michael Anthony), 1973- (New York : Hyperion, 2010)
Short stories, journal entries, family records, and letters maintained by the Repository of History, the center of the Blue Blood's power, reveal secrets of Manhattan's vampire elite dating to the dawn of history.
Keywords: Vampires -- Fiction; Wealth -- Fiction; Secrets -- Fiction; New York (N.Y.) -- Fiction